PERBANDINGAN LAMA PERENDAMAN BUBU DASAR MENGGUNAKAN TUTUPAN DAUN KELAPA TERHADAP HASIL TANGKAPAN IKAN DI TELUK KELABAT DESA PUSUK BANGKA BARAT - Edi Setiyono; Wahyu Adi; Kurniawan Kurniawan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Pusuk village located in the district of West Bangka Regency in Kelapa. Most of the village pusuk fishermen who actively conduct arrests in Gulf waters Kelabat. The use of fishing gear to catch fish traps base has long been used by the fishing village of Pusuk. The purpose of this study was to determine the number, type and weight of the fish battom trap cover use coconut leaf and determine the soaking time effective trap with coconut leaf cover against fish catches. The method used is the method of experimental fishing trials with traps soaking time difference of four days, five days and six days. The catch for the research was obtained as many as 11 species, by weight and the amount of soaking time obtained a four-day haul of 67.87 kg with tail number 1093, a five-day immersion of 65.35 kg with tail number 1024 and six-day immersion of 43.56 kg with the number 765 tail. Immersion bubu four-day gain the most catches by weight during the study, an effective option and give a significant effect on catches